Analysis of Perceived Usefulness and Perceived Ease of Use to the Actual System Usage through Attitude Using Online Guidance Application - Muhammad Mitsal Islami; Muhammad Asdar; Andi Nur Baumassepe (Hasanuddin Journal of Business Strategy, 2021)
This study aims to analyze the effect of perceived usefulness and perceived ease of use on actual system usage through attitude toward using the Ruangguru online learning guidance application in Makassar City. This study took data directly from students who subscribed to the Ruangguru application by taking 247 high school students and their equivalent as samples in this study. To implement the objectives of this study used analysis techniques using path analysis. The results of the analysis prove that perceived usefulness and perceived ease of use have a positive and significant effect on attitude toward using the Ruangguru online tutoring application. Meanwhile, perceived usefulness, perceived ease of use, and attitude toward using have a positive and significant effect on actual system usage in the Ruangguru online tutoring application. Based on the results of the single test, attitude toward using is able to mediate the effect of perceived usefulness and perceived ease of use on actual usage in the Ruangguru online tutoring application.